2020
DOI: 10.1186/s12894-020-0574-1
|View full text |Cite
|
Sign up to set email alerts
|

The utility of intravenous ketamine for the management of intraoperative penile erection: a retrospective single-center analysis of endourological surgeries over a 4-year

Abstract: Background: To assess the prevalence of intraoperative penile erection in our endourology practice and the utility of intravenous ketamine in the management of the condition. Methods: Of 402 endoscopic urological procedures performed in our clinic over a 4-year (2015-2019) period, a total of 9 cases with intraoperative penile erection impeding instrumentation during endourological surgery were included. Data on patient age, weight, height, American Society of Anesthesiologists (ASA) physical status classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(37 reference statements)
0
4
1
Order By: Relevance
“…Since then, we still have encountered a few cases of penile erection in patients undergoing urethroscopic procedures. However, it has been reported that penile erection under spinal or general anesthesia at the time of urethroscopic surgery occurs at a reported incidence of 0.1-2.4% [4]. However, by our estimation, it does not feel like that the rate of penile erection with remifentanil is not lower than the previously reported ones.…”
Section: Open Accesscontrasting
confidence: 81%
See 1 more Smart Citation
“…Since then, we still have encountered a few cases of penile erection in patients undergoing urethroscopic procedures. However, it has been reported that penile erection under spinal or general anesthesia at the time of urethroscopic surgery occurs at a reported incidence of 0.1-2.4% [4]. However, by our estimation, it does not feel like that the rate of penile erection with remifentanil is not lower than the previously reported ones.…”
Section: Open Accesscontrasting
confidence: 81%
“…To the best of our knowledge, this is the first report of remifentanil-induced penile erection in elderly patients undergoing urethroscopic procedures. Because urethroscopic surgery is usually performed under spinal anesthesia without the use of remifentanil and penile election is rarely seen under spinal anesthesia [4], intraoperative penile erection by remifentanil is hardly detectable. However, it should be understood that this phenomenon can occur in not only male children and young adults, but also elderly patients.…”
Section: To the Editormentioning
confidence: 99%
“…Partial or complete erection during general anesthesia in urologic surgery is a relatively rare but challenging condition with an incidence of 0.1 to 2.4%. While the cause is unknown, it is generally possible that stimulating the penis while preparing the skin or the tool used for the procedure may be the main cause of the erection (2).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] This makes the penile instrumentation cumbersome resulting in difficulty to perform the procedure safely, thus exposing the patient to a greater risk of complications such as urethral trauma, bleeding, and stricture formation. [ 1 2 ] Rarely, it may lead to postponement of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported the use of intravenous ketamine, glycopyrrolate, dexmedetomidine, and terbutaline,[ 2 8 9 10 ] and some have reported inhalation of salbutamol[ 11 ] for managing intraoperative erection.…”
Section: Introductionmentioning
confidence: 99%